Pengembangan LKPD Larutan Penyangga Berbasis Guided Discovery Learning dengan Tiga Level Representasi Kimia untuk Kelas XI SMA - Azizah Arta; Minda Azhar (Universitas Negeri Padang, 2019)
LKPD are one of the learning materials that can be used in the learning process. Buffer solution LKPD based on guided discovery learning with three levels chemistry representation. The type of this research was Research and Development (R and D) with the 4D development model. 4-D models that consist of four steps: define, design, develop, and disseminate. The research was limited on develop step. The research instrument that used questionnaire in the form of validity and practicality sheet. The LKPD was validated by three UNP chemistry lectures and two chemistry teachers of SMAN 5 Padang. The LKPD was practicalited by two chemistry teachers and 28 students XII MIPA 1 of SMAN 5 Padang. Data were analyzed by Cohen Kappa formula. The result of validity test showed that the LKPD had a very high validity category (k = 0,86). Practicality test result showed that the LKPD has very high practicality category (k = 0,80 dan k = 0,82). The LKPD was valid and practical.